LEARNING COUNT WORDS AS AN EXAMPLE OF THE STORY "THIEF" BY ABDULLAH QAHOR (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In this article, it will be explained about the counting words taught in the mother tongue textbook, their types and ways of use and places based on the story "Thief" by Abdulla Qahhor. Each account used in the story is subjected to word analysis and compared in terms of its activity in other literatures and its activity in styles.